Understanding American government - Welch, Susan (Thomson/Wadsworth, 2008)
Written by authors who have won numerous awards for their research and writing on women and minority issues in American Government, this textbook offers an inclusive view of participants in the American political system. From this book, you will not only learn how government works but you will move on to the more controversial aspects of government, being exposed to actual people and experiences of government in action through the You Are There feature that opens each chapter, the suggested film lists at the ends the chapters, and the online exercises that support and enhance concepts found throughout the text.